فقہ المقارن میں یوسف القرضاوی کے منہج کا جائزہ اور اس کے معاشرتی اثرات: An Overview of Yusuf al-Qaradawi's Methodology in Alfiqh al-Muqāran (Comparative Jurisprudence) and its Social Impact - admin, Dr. Abdul Ghaffar; Monaza Bilal (Al-Amīr Research Journal for Islamic Studies, 2025)
Alfiqh al-Muqāran is an accomplishment of Yusuf Al-Qaradawi which engages with modern legal challenges without compromising Islamic principles. His insights of Islamic jurisprudence created harmony among different schools of thought of jurisprudence. Alfiqh al-Muqāran had great impact on Muslim society. His insights contributed in providing solutions regarding social harmony, women’s rights and social justice. His approach ensures that Islamic law remains relevant in addressing contemporary societal needs. By examining Al-Qaradawi’s comparative jurisprudence and its societal impact, this research aims to provide future generations with a structured methodology to ensure continuation of this legacy. Understanding his jurisprudential approach will equip modern scholars with the tools to develop progressive legal solutions while maintaining Islamic authenticity. This study underscores the importance of Fiqh al-Muqāran as a dynamic field capable of fostering social progress and intellectual growth. Keywords: Fiqh al-Muqāran, Islamic Jurisprudence, Legal Adaptability, Modern Islamic Thought, Societal Impact, Islamic Legal System